One step synthesis of ethyl levulinate biofuel by ethanolysis of renewable furfuryl alcohol over hierarchical zeolite catalyst - Nandiwale, Kakasaheb Y.; Pande, Ashwini M.; Bokade, Vijay V. (RSC Advances, 2015)
Ethanolysis of renewable furfuryl alcohol (FAL) to ethyl levulinate (EL) biofuel over various zeolites viz. H-ZSM-5 (microporous, medium pore), Hierarchical-HZ-5 (combination of micro-and meso pore), H-Beta (microporous, large pore) and Ultra Stable Y (USY, microporous, large pore) was studied in detail. To the best of our knowledge, probably for the first time, Hierarchical-HZ-5 synthesized by desilication post-treatment has been employed as a heterogeneous catalyst for ethanolysis of FAL. The synthesized catalysts were characterized by powder X-ray diffraction (PXRD), temperature programmed NH3 desorption (TPAD), Energy dispersive X-ray analysis (EDAX), etc. Response surface methodology (RSM) with Box-Behnken experimental design (BBD) was used to investigate the influence of three crucial process variables of ethanolysis such as ethanol to FAL molar ratio, percent catalyst loading and reaction temperature on EL yield. The optimization tool of design expert software was employed to obtain the optimum reaction parameters for FAL ethanolysis over Hierarchical-HZ-5 catalyst. Three intermediates of FAL ethanolysis reaction such as, ethoxymethylfuran (EMF), 4,5,5-triethoxypentan-2-one and diethyl ether (DEE) have been identified and quantified from the product mixture with the aid of Gas Chromatography-Mass Spectroscopy (GC-MS). Hierarchical-HZ-5 was found to be a potential catalyst for ethanolysis of FAL with 73% EL yield and 26% EMF yield at optimized process parameters.

HPW anchored Meso-HZ-5, a novel catalyst for selective synthesis of ethyl levulinate biofuel by alcoholysis of biomass-derived furfuryl alcohol - Nandiwale, Kakasaheb Y.; Pande, Ashwini M.; Bokade, Vijay V. (Environmental Progress & Sustainable Energy, 2018)
Ethanolysis of biomass derived furfuryl alcohol (FA) produces ethyl levulinate (EL), a biofuel additive and precursor for -valerolactone synthesis. The present study is devoted to develop an efficient and an environmentally benign catalytic system for one-pot conversion of FA to EL biofuel, by revealing an insight of the catalytic mechanism. The catalytic activity of H-ZSM-5, Meso-HZ-5 (desilicated H-ZSM-5) and different percentage H3PW12O40(HPW) anchored to Meso-HZ-5 catalysts have been evaluated for the FA ethanolysis. As per our knowledge, this is the first research reporting the application of HPW anchored to Meso-HZ-5 catalysts for the conversion of FA into EL in biomass utilization. These catalysts were synthesized and characterized by Powder X-ray diffraction (XRD), N-2 physisorption and temperature programmed NH3 desorption (TPAD). Products of FA ethanolysis viz., 4,5,5-triethoxypentan-2-one (TEP), ethoxy-methyl- furan (EMF), diethyl ether (DEE), EL were identified by Gas Chromatography-Mass Spectroscopy (GC-MS) and quantified by flame ionization detector (GC-FID). The physicochemical properties of catalysts were found to correlate to the product distribution matrix. Moreover, influences of several process parameters such as catalyst amount, reactant molar ratio, temperature and time on the extent of FA ethanolysis were systematically investigated. Under optimized conditions, 15% (w/w) HPW/Meso-HZ-5 exhibited a remarkable catalytic performance with complete FA conversion (100%) along with 97% yield of EL, these activity values are superior than the previously reported studies. The present study provides an insight of the catalytic mechanism along with a potential environmental benign and the economic catalyst for the efficient synthesis of EL biofuel from the biomass-derived FA